RANCANG BANGUN PROTOTIPE PEMBANGKIT LISTRIK TENAGA SURYA DENGAN SOLAR TRACKER SYSTEM BERBASIS IOT - Kresna Aditya, I Putu Gede; Satya Kumara, I Nyoman; Setiawan, I Nyoman (Jurnal SPEKTRUM; Vol 10 No 4 (2023): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2023.v10.i04.p20, 2023)
Water is an essential requirement for agricultural land and can be obtained from various sources depending on its geographical location. The Keliki Village Farmers Group in Subak Malikoda faces the challenge of drought, resulting in a shortage of water supply during the dry season. In this research, a Solar Irrigation Pump (SIP) with a solar tracker system is designed to pump groundwater with the aim of enhancing irrigation water supply for Subak Malikoda during the dry season. The solar-powered irrigation pump system design consists of an 18.5 kW submersible pump coupled with a 23.1 kWp PV system using 60 monocrystalline solar modules equipped with a solar tracker and a 30 kW inverter. Based on the analysis conducted, the PVSyst results for the SIP without a solar tracker show that the pump can operate for 6,067 hours with an average water discharge of 274.9 m3/day. This is based on the received global effective irradiation of 1765.1 kWh/m2 in one year. However, with the use of the solar tracker system, the pump can operate for 6,933 hours with a water discharge of 305.2 m3/day and global effective irradiation of 1963.8 kWh/m2 in one year. The analysis concludes that the SIP with a solar tracker system can operate optimally and fulfill the water discharge requirements of Subak Malikoda. This makes the solar tracker system an effective solution to enhance the water supply for Subak Malikoda during the dry season.